Significance of subcentimetre 18F-FDG PET/CT pulmonary abnormality in patients with known extrapulmonary malignancy. - Ahmad Saad , Fathinul Fikri; Lau, W.F.E. (University of Malaya, 2010)
The significance of a subcentimetre 18F-FDG PET/CT pulmonary abnormality in a patient with known extrapulmonary primary malignancy can have a major impact on the clinical management of the patient. The clinician’s reliance on the semi-quantitative and qualitative PET/CT analysis of the abnormality has, at times, led to untoward diagnostic problems, given the limited spatial resolution of PET for a small volume lesion performed as part of the standard PET/CT study. This paper highlights a case each of an FDG-positive and an FDG-negative focal pulmonary abnormality in a combined PET/CT study of patients with known extrapulmonary malignancy.